Analytical Method Validation and Formula Optimization of Topical Nanoemulsion Formulation Containing Resveratrol - Christofori Maria Ratna Rini Nastiti; Florentinus Dika Octa Riswanto (Indonesian Journal of Chemistry, 2021)
Resveratrol (RSV), a natural lipophilic phytoalexin, was reported as an antioxidant and anti-inflammatory agent, which has the potential to cure diabetic wounds. However, several studies suggested the limitation of RSV, such as poor aqueous solubility, poor stability, and poor oral bioavailability. To overcome the issues, RSV was formulated as a topical nanoemulsion. It is important to ensure the quality of the dosage form by evaluating RSV load in the nanoformulation and optimizing the formula. A reversed-phase HPLC method was developed and validated prior to the load determination of RSV in the nanoemulsion formulation. The composition of triacetin-eugenol, Kolliphor® RH 40, and Transcutol® was further optimized by employing a Box-Behnken Design (BBD) to achieve the optimum composition with expected viscosity and RSV load. The HPLC method for determining RSV load was successfully validated for parameters of selectivity with the resolution of 8.487, linearity and range (r = 0.9979), precision (0.12% of RSD), accuracy (109–110% of recovery), the limit of detection (0.574 µg/mL), and limit of quantitation (1.740 µg/mL). The result of formula optimization was promising, showing the optimum composition of triacetin-eugenol, Kolliphor® RH 40, and Transcutol® at 4.44 g, 30.97 g, and 11.39 g, respectively.